2011
DOI: 10.1039/c0nr00709a
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale coordination polymers exhibiting luminescence properties and NMR relaxivity

Abstract: This article presents the first example of ultra-small (3-4 nm) magneto-luminescent cyano-bridged coordination polymer nanoparticles Ln0.33(3+)Gdx3+/[Mo(CN)8]3- (Ln=Eu (x=0.34), Tb (x=0.35)) enwrapped by a natural biocompatible polymer chitosan. The aqueous colloidal solutions of these nanoparticles present a luminescence characteristic of the corresponding lanthanides (5D0→7F0-4 (Eu3+) or the 5D4→7F6-2 (Tb3+)) under UV excitation and a green luminescence of the chitosan shell under excitation in the visible r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 84 publications
0
36
0
Order By: Relevance
“…Fluorescence imaging is suitable for small animal imaging but has many shortcomings in clinical applications because of the limited tissue penetration of light. MR imaging, together with other 3D whole body imaging techniques, would be preferred in the clinic to determine the exact tumor locations, sizes, and shapes, which are valuable information particularly important for the treatment planning in phototherapies . We and others have found that porphyrin structures could serve as the chelate ligand to capture metal ions such as Mn 2+ and Gd 3+ to offer contrast in MR imaging .…”
Section: Resultsmentioning
confidence: 99%
“…Fluorescence imaging is suitable for small animal imaging but has many shortcomings in clinical applications because of the limited tissue penetration of light. MR imaging, together with other 3D whole body imaging techniques, would be preferred in the clinic to determine the exact tumor locations, sizes, and shapes, which are valuable information particularly important for the treatment planning in phototherapies . We and others have found that porphyrin structures could serve as the chelate ligand to capture metal ions such as Mn 2+ and Gd 3+ to offer contrast in MR imaging .…”
Section: Resultsmentioning
confidence: 99%
“…CPT was freshly dissolved in ethanol (0.5 mg mL −1 ) and put in an ultrasonic bath until complete dissolution and the cells were treated with increasing concentrations of CPT (0.5–3 μg mL −1 ). Then, a MTT assay was performed to evaluate the toxicity 27. Briefly, cells were incubated for 4 h with MTT (0.5 mg mL −1 , 3‐(4,5‐dimethylthiazol‐2‐yl)‐2,5‐diphenyltetrazolium bromide; Promega) in media.…”
Section: Methodsmentioning
confidence: 99%
“…In a distinct study, Chelebaeva et al designed a straightforward method to prepare ultrasmall (3–4 nm) magnetoluminescent polymer NPs enwrapped by chitosan. This approach is based on an association of luminescent Ln 3+ and paramagnetic Gd 3+ ions with paramagnetic octacyanomolybdate building blocks to obtain biocompatible and high‐stable NPs, even at low pH.…”
Section: Chitosan‐derived Luminescent Materialsmentioning
confidence: 99%